2011
DOI: 10.1115/1.4003353
|View full text |Cite
|
Sign up to set email alerts
|

Vibration of Single- and Double-Layered Graphene Sheets

Abstract: Free vibration of single- and double-layered graphene sheets is investigated by employing nonlocal continuum theory and molecular dynamics simulations. Results show that the classical elastic model overestimated the resonant frequencies of the sheets by a percentage as high as 62%. The dependence of small-scale effects, sizes of sheets, boundary conditions, and number of layers on vibrational characteristic of single- and double-layered graphene sheets is studied. The resonant frequencies predicted by the nonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…They showed that the local plate model overestimates the resonant frequencies of the sheets with a percentage difference up to 62% at sizes of 2.47 nm. 92 Their results showed that the difference between local and nonlocal plate models remains significant in all aspect ratios as presented in Figure 5, and the overestimation is around 50% at aspect ratio of a=b ¼ 4. Therefore, the nonlocal plate model is strictly necessary for the rectangular GSs with a short side.…”
Section: A Resonant Frequenciesmentioning
confidence: 84%
See 3 more Smart Citations
“…They showed that the local plate model overestimates the resonant frequencies of the sheets with a percentage difference up to 62% at sizes of 2.47 nm. 92 Their results showed that the difference between local and nonlocal plate models remains significant in all aspect ratios as presented in Figure 5, and the overestimation is around 50% at aspect ratio of a=b ¼ 4. Therefore, the nonlocal plate model is strictly necessary for the rectangular GSs with a short side.…”
Section: A Resonant Frequenciesmentioning
confidence: 84%
“…Their simulation results show that the magnitudes of the smallscale parameter are 1.41 nm and 0.87 nm for simply supported and clamped graphenes, respectively. Arash and Wang 92 investigated free vibrations of SLGSs and doublelayered GSs (DLGSs) with different boundary conditions using the nonlocal plate model and MD simulations. They showed that the local plate model overestimates the resonant frequencies of the sheets with a percentage difference up to 62% at sizes of 2.47 nm.…”
Section: A Resonant Frequenciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Bending, vibration, and buckling of rectangular and circular GSs have been studied by different researchers [24][25][26][27][28][29][30][31][32][33][34]. For example, Arash and Wang [35] investigated the vibration of single-and doublelayered graphene sheets (SLGSs and DLGSs) using the nonlocal elasticity theory and molecular dynamics simulations. The nonlocal parameter was calibrated through the verification of natural frequency obtained by the nonlocal elasticity theory and molecular dynamics simulations.…”
Section: Introductionmentioning
confidence: 99%